Taoist Aesthetics Perspective: Cultural Consciousness and Innovation in Craft Design - Ma, Yuxin (International Journal of Global Economics and Management, 2024)
This research investigates the application of Taoist aesthetics in modern craft design, meeting the demand for individualized cultural products. It reviews Taoist principles—"nature," "non-action," and "simplicity"—and their reflection in design, emphasizing harmony with nature and a minimalist design philosophy. The research demonstrates the contribution of Taoist philosophy to the enrichment of design principles, providing innovative direction to designers while honoring and integrating traditional cultural elements with contemporary preferences.